A novel dynamic stabilization and vibration isolation structure inspired by the role of avian neck. (1st March 2021) - Sun, Xiuting; Wang, Feng; Xu, Jian
Highlights: Propose a novel multi-layer structure bio-inspired by the role of avian neck. Realize enough static loading capacity and zero dynamical stiffness simultaneously. Obtain design criteria of configuration and parameters for wide-band vibration isolation. Achieve stabilization effectiveness for excitation with low-frequency and displacement mutation. Abstract: A novel multi-layer structure with functions for dynamic stabilization and vibration isolation, bio-inspired by the role of an avian neck, is proposed in this paper. Inspired by the fact that an avian neck can stabilize the head from body flapping, we expect that the proposed structure can achieve dynamic stabilization effectiveness under external excitation with a low frequency, large amplitude, and displacement mutations. First, for different configurations of the bio-inspired structure, the key characteristics, such as the elastic deformation energy, restoring force and equivalent dynamic properties are determined by mechanical modeling. It discovers that the proposed bio-inspired structure could achieve the designed loading capacity and dynamic zero stiffness simultaneously. Then according to the analysis of the dynamic behaviors under impact excitation and harmonic excitation by the perturbation method, the optimum criteria for the structural configuration and parameters are carried out. Thus, the effective isolation band begins at zero frequency, and the dynamic behavior could be quickly stabilized. Finally, the constructed multi-layer structure could achieve the stabilization functions of the avian neck. For different strengths of gusts, the amplitude of the top layer is less than a fifth of the excitation from the body. Due to the multiple functions in dynamic stabilization and control, the proposed structure can solve the bottleneck techniques in nonlinear isolation structural design, and it has remarkable potential applications in the fields of mechanical arms, sensors in satellites, etc. Graphical abstract: Image, graphical abstract